Thermal, mechanical and rheological properties of poly (lactic acid)/epoxidized soybean oil blends - Ali, Fathilah; Chang, Young-Wook; Kang, Shin Choon; Yoon, Joon Yong (Springer, 2009)
Poly(lactic acid) (PLA) was melt blended with epoxidized soybean oil (ESO) in an internal mixer and thermal, mechanical and rheological properties of the blends were investigated by means of differential scanning calorimetry, dynamic mechanical analysis, tensile test and small amplitude oscillatory shear rheometry. ESO lowered glass transition temperature and increased the ability of PLA to cold crystallization. The blend exhibited improved elongation-at-break along with a plastic deformation. The plasticization effect by ESO was also manifested by the lowering of dynamic storage modulus and viscosity in the melt state of the blends compared with neat PLA.